PENGARUH INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN DI LUSI DAN PAKAN BY THE RIVER BALI - Marchya Ayu, Nadia; Kusuma Negara, I Made; Suardana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024)DO - 10.24843/IPTA.2024.v12.i01.p13, 2024)
In this research, several factors will be discussed that can influence purchasing decisions at Lusi and Pakan by The River Bali, including content creation, content sharing, and connecting. The purpose of this study was to determine the effect of content creation, content sharing, and connecting on purchasing decisions at Lusi and Pakan by The River Bali. This research is a quantitative descriptive study with samples taken by purposive sampling of 100 respondents with the criteria of having an Instagram account and having made purchases at Lusi and Pakan by The River Bali. The data analysis technique used is descriptive statistical analysis with a Likert scale, validity test, reliability test, classic assumption test, multiple linear regression analysis, analysis of the coefficient of determination, t test, and f test using the IBM SPSS Statistics Version 26 for Windows program. The results of this study indicate that the content creation variable has a positive and significant influence on purchasing decisions with a coefficient of 0.332 (33.2%), the content sharing variable has a positive and significant influence on purchasing decisions with a coefficient of 0.187 (18.7%) , the connecting variable has a positive and significant effect on purchasing decisions with a coefficient of 0.375 (37.5%) and the variables content creation, content sharing, and connecting simultaneously show that it has a positive and significant effect with a determination coefficient of 0.642 (64.2 %).